Relationship of maxilla to cranial base in different facial types–a cephalometric evaluation - Tarun Rana; Rohit Khanna; Tripti Tikku; Kiran Sachan (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: Background: Many conflicting opinions have been put forth in the dental literature concerning the maxilla and its relationship to craniofacial complex. In view of this fact, this cephalometric study was conducted to determine the relationship of maxilla to cranial base in different facial types. Materials and Methods: The sample consists of 120 pretreatment lateral cephalogram, which were categorized into three groups, normodivergent, hypodivergent, and hyperdivergent. Each group consists of 20 males and 20 females. Descriptive statistics for 11 variables were calculated. Results and Conclusion: The result of this study implies that in hyperdivergent subjects' sagittal maxillary base size was smaller and upper posterior facial height (UPFH) was increased in comparison to hypodivergent and normodivergent subjects. Upper posterior facial height has positive correlation with anterior facial height. Posterior maxillary position in relation to cranial base increases with increase in cranial flexural angle in hypodivergent subjects and vice versa in hyperdivergent subjects. Upper posterior facial height decreases with increase in cranial flexural angle in hypodivergent subjects and vice versa in hyperdivergent subjects.